The Role of Emotional and Rational Trust in Explaining Attitudinal and Behavioral Loyalty: An Insight Into SME Brands - Chuan Huat Ong; Salniza Md. Salleh; Rushami Zien Yusoff (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
Brand trust is a powerful asset for Small and Medium size Enterprises (SMEs) to retain good relationships with their loyal customers, to ensure their long term survival. However, SME managers first need to understand the consequences of the two unique emotional and rational components of trust on attitudinal and behavioral loyalty, because both loyalty dimensions have unique consequences for a brand’s performance. Hence, this study aims to answer two research issues: (1) Do brand intentions and brand reliability influence both attitudinal loyalty and behavioral loyalty? (2) Which component of trust explains attitudinal and behavioral loyalty more? Data were obtained from 210 customers through the use of an intercept survey method on successful SME brands in the restaurant industry. The findings revealed that emotional and rational trust influenced both attitudinal and behavioral loyalty. Despite that, customers have a higher tendency to exhibit attitudinal and behavioral loyalty when a brand can be relied upon to deliver on its promises.